FREKUENSI PENILAIAN FOMATIF DAN KEMANDIRIAN BELAJAR - SUPARDI U. S. (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2011)
The objective of the study was to know the effects of interaction between formative assessment frequency and learning independence toward Calculus learning outcomes with controlling university students’ prior capacity. Research using experimental methods with 2 x 2 treatment by level design, and can be concluded from the finding, that with controlling university students’ prior capacity: (1) the group with high learning independence and was given formative assessment each subject matter got lower score on calculus learning outcomes than the group was given conventional formative assessment, (2) the group with low learning independence and was given formative assessment each subject matter got higher score calculus learning outcomes than the group was given conventional formative assessment, (3) the group was given formative assessment each subject matter and have high learning independence got lower score calculus learning outcomes than the have low learning independence, and (4) the group was given conventional formative assessment and have high learning independence got higher score calculus learning outcomes than the low learning independence. The result showed that there was interaction between formative assessment frequency and and learning independence toward Calculus learning outcomes with controlling university students’ prior capacity. To improve the quality of Calculus learning outcomes, the lecturers were supposed to evaluate the university stuents’ using formative assessment variously. It must be matched with level of the learning independence of university students’.